Implementasi Kurikulum Merdeka Pada Pembelajaran Fiqih Kelas X di MAN 2 Wonosobo - Khusniatul Khuluqi; Ahmad Zuhdi; Hidayatu Munawaroh (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
Curriculum renewal is a reality that is currently occurring in educational development in Indonesia. One of them is the Independent Curriculum which is currently being developed. The concept of independent learning was initiated by Nadiem Makarim which can be a solution or problem that teachers have been facing. In implementing the Independent Curriculum, it is important for every educator to emphasize the freedom, independence and creativity of students. It is important to understand this emphasis approach to the study of fiqh. Learning fiqh is important because a student’s ability to understand and laearn religion is not only related to understanding. With the Merdeka Curriculum, it is hoped that fiqh lessons can be understood more easily and have more fun. The purpose of this research is to: 1) to determine class X fiqh learning at Madrasah Aliyah Negeri 2 Wonosobo; 2) to find out the implementation of the independent curriculum in class X fiqh learning at Madrasah Aliyah Negeri 2 Wonosobo; 3) to determine the supporting and inhibiting factors for implementing the independent curriculum in class X fiqh learning at Madrasah Aliyah Negeri 2 Wonosobo. The method used in this research is descriptive. Data collection techniques use observation methods, interview methods, and documentation methods.